2009
DOI: 10.1038/hr.2009.192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the long-term effects of candesartan and olmesartan on plasma angiotensin II and left ventricular mass index in patients with hypertension

Abstract: In general, treatment with most angiotensin receptor blockers (ARBs) increases plasma angiotensin II (Ang II) level because of a lack of negative feedback on renin activity. Olmesartan is a potential ARB inducing activation of angiotensin-converting enzyme 2 (ACE2) that hydrolyzes Ang II to Ang 1-7, and has shown a beneficial effect on ventricular remodeling. Indeed, a previous study reported that olmesartan treatment resulted in decreased plasma levels of Ang II and aldosterone. However, there has not yet bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…On the basis of those experimental studies, olmesartan and candesartan offered similar benefits for mechanical stressinduced ERKs activation, but there was a different clinical outcome in the Tsutamoto's study. 3 In contrast, there was a similar clinical outcome among ARBs, even though ARBs have different benefits on the basis of experimental studies. The presence of molecular effects for each ARB, according to experimental studies, does not necessarily reflect the clinical outcome.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…On the basis of those experimental studies, olmesartan and candesartan offered similar benefits for mechanical stressinduced ERKs activation, but there was a different clinical outcome in the Tsutamoto's study. 3 In contrast, there was a similar clinical outcome among ARBs, even though ARBs have different benefits on the basis of experimental studies. The presence of molecular effects for each ARB, according to experimental studies, does not necessarily reflect the clinical outcome.…”
mentioning
confidence: 88%
“…25 In contrast, telmisartan was more beneficial for improving glucose and lipid profiles. 26 In conclusion, clinical trials, including that of Tsutamoto et al, 3 have shown that ARBs have different degrees of benefits. Some effects may be due to molecular effects, whereas most of the benefits conferred by ARBs are class effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease rate of LVMI was significantly higher after one year of the administration, and the decrease rates of angiotensin II and LVMI were correlated in the olmesartan group. 15) In an acute stage study of healthy individuals, olmesartan significantly lowered aldosterone, significantly increased the renin activity and showed an improvement in arterial compliance. 4) Few reports have appeared on the RAAS in relation to olmesartan, but as described previously, there have been reports on decreases in angiotensin II or aldosterone and also reports on decreases in both angiotensin II and aldosterone.…”
Section: Discussionmentioning
confidence: 99%